Penetration of Microplastics (Polyethylene) to Several Organs of Nile Tilapia (Oreochromis niloticus). Issue 1 (March 2021) - Aryani, D; Khalifa, M A; Herjayanto, M; Solahudin, E A; Rizki, E M; Halwatiyah, W; Istiqomah, H; Maharani, S H; Wahyudin, H; Pratama, G
Abstract: Microplastics are a severe problem in several countries. Microplastics spread throughout the ecosystem both on aquatic and terrestrial. Those are very difficult to overcome as well as have an impact on the environment and affect food safety. This study aimed to know the penetration of microplastics into several organs in Nile tilapia. The experiment was conducted by given 30 grams of microplastic (a type of polyethylene scrub) into an aquarium (15 L) containing five fish (consumption size) for seven days. The results showed that microplastic penetration occurred in the blood, gills, gonads, intestines, liver, muscles, and stomach. These results explain that during a week of rearing, the fish have been exposed to microplastics. It was very dangerous for human health issues if consumed.